Antioxidant Activity of Ethanol Extract of Secang Wood (Caesalpinia sappan L.), Gotu Kola (Centella asiatica L.), and Their Combinations with DPPH Assay - Binti Maulina Putri; Sugiarto; Brian Wasita; Ratih Puspita Febrinasari (LPPM Universitas Duta Bangsa Surakarta, 2021)
Antioxidants are the properties of active compounds that can prevent the formation or binding of free radicals and other molecules and inhibit oxidation reactions. Secang wood (Caesalpinia sappan L.) and Gotu kola (Centella asiatica L.) are plants that contain lots of phytochemical compounds used as traditional drinks such as steeping drinks to date. Combining several natural ingredients is believed to provide more benefits and a more effective dosage if used properly. This study aims to determine the antioxidant activity of the ethanol extract of secang wood and gotu kola and their combinations (1:1, 2:1, 1:2) based on the IC50 value with various concentrations and replication 3 times for each sample from the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Ascorbic acid was also used as a positive control for this assay. Secang wood and gotu kola were extracted using maceration method with 96% ethanol as solvent. The results showed that the IC50 antioxidant activity of 34.173 ppm of secang wood ethanol extract was more active (very strong) compared to 160.236 ppm of gotu kola extract (weak). The best combination of ethanol extract mixture of secang wood and gotu kola which resulted in the strongest activity among the three combinations was a 1:1 ratio of 59.431 ppm (strong).